The Forgotten Stoppa Procedure: An Alternative Approach for Incarcerated Groin Hernia Following Prior Anterior Repair Unsuitable for Laparoscopic Surgery – Case Series - Normasari, Rena; Fardiansyah, Mochamad Syahroni; Lesmana, Tomy (Faculty of Medicine, Universitas Jember, 2025)
Incarcerated and recurrent inguinal hernias present complex surgical challenges, particularly in patients with a history of multiple anterior repairs or contraindications to laparoscopic approaches. Although minimally invasive techniques such as Transabdominal Preperitoneal (TAPP) and Totally Extraperitoneal (TEP) repair have become standard practice, not all patients are ideal candidates due to altered anatomy, dense adhesions, or comorbidities that preclude general anesthesia. In such cases, the Stoppa procedure—a classical open posterior approach with wide preperitoneal mesh placement—offers a safe and effective alternative. This case series describes two elderly male patients with incarcerated recurrent inguinal hernias following multiple prior anterior mesh repairs. Both presented in emergency settings with significant comorbidities, making laparoscopic surgery unfeasible. Surgical repair was performed using a lower midline incision and extensive preperitoneal dissection, followed by the placement of a large polypropylene mesh without extensive fixation. In both cases, the incarcerated ileal segments were viable and successfully reduced without bowel resection. Postoperative recovery was uneventful, with both patients discharged within three days and showing no recurrence or major complications during a one-year follow-up. These outcomes demonstrate that the Stoppa technique remains a valuable option in complex cases where anterior or laparoscopic approaches are unsuitable. Its anatomical logic, broad coverage, and reduced risk of chronic pain support its continued role in modern hernia surgery. Surgeons should retain proficiency in this underutilized yet highly effective method, particularly when managing high-risk or reoperative groin hernias.